2007
DOI: 10.1007/s00418-007-0279-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of Peroxisome proliferator-activated receptor-delta (PPAR-delta) in mouse tissues using tissue microarray

Abstract: Peroxisome proliferator-activated receptor-delta (PPAR-delta) is known as a transcription factor involved in the regulation of fatty acid oxidation and mitochondrial biogenesis in several tissues, such as skeletal muscle, liver and adipose tissues. In this study, to elucidate systemic physiological functions of PPAR-delta, we examined the tissue distribution and localization of PPAR-delta in adult mouse tissues using tissue microarray (TMA)-based immunohistochemistry. PPAR-delta positive signals were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 22 publications
(29 reference statements)
9
45
0
Order By: Relevance
“…It is hypothesized that this may be due to an insufficient number of PPARb/d receptors in lung tissue. Indeed, immunohistochemical analysis demonstrated only weak PPARb/d receptor immunoreactivity in lung alveolar type II cells and bronchial epithelium [5]. It was therefore of interest to examine RNA from BALF-derived inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that this may be due to an insufficient number of PPARb/d receptors in lung tissue. Indeed, immunohistochemical analysis demonstrated only weak PPARb/d receptor immunoreactivity in lung alveolar type II cells and bronchial epithelium [5]. It was therefore of interest to examine RNA from BALF-derived inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…PPARb/d has been less well described as compared to the other isoforms. Higashiyama et al [5] have shown that PPARb/d is ubiquitously expressed in a variety of tissues including liver, adipose tissue, skeletal muscle, kidney, cerebellum, thalamus, cerebellar cortex and intestine. Physiologically, PPARb/d has been associated with adipocyte precursor cell proliferation [6], oligodendrocyte differentiation [7], and cholesterol homeostasis [8].…”
Section: Introductionmentioning
confidence: 99%
“…PPARδ is a member of PPAR family that belongs to the nuclear hormone receptor superfamily and is also a liganddependent transcription factor. PPARδ is expressed in diverse tissues (15), and its expression level is very high in the GI tract compared with other tissues (16). Although PPARδ has been shown to be involved in chronic inflammation and in CRC progression, its role is still unclear and vigorously debated (17).…”
mentioning
confidence: 99%
“…Comparisons of the results of the process with manual quantiWcations carried out by a trained analyst showed a high degree of accuracy and reliability of the process, and indicated that the method is not only more objective and faster than manual quantiWcation, but also applicable to digital images with high complexity. Another method which has marked a signiWcant advance in pathological analyses and in basic research is the tissue microarray (TMA), which allows high-throughput histomorphologic analysis of tissues with respect to RNA or protein content in situ (e.g., Higashiyama et al 2007;Farragher et al 2008). However, manual reviews of the assays are timeconsuming, highly subjective and, at best, semiquantitative.…”
Section: Speciwc Applications Of Imagingmentioning
confidence: 99%